A social marketing campaign to educate University of Wisconsin-La Crosse students about signs of emotional distress and community mental health resources - Lundgren, Nicole (My University, 2017)
In light of the mental health crisis in America, the purpose of this project was to educate University of Wisconsin-La Crosse (UWL) students about the five signs of emotional distress and provide them with on-campus, community, and national resources that would offer mental health support for themselves and others. If students are able to 3 recognize when someone is suffering, they can begin to connect, reach out, offer help, or inspire hope to someone in a time of need. Moreover, if we can begin to dissolve the stigma that surrounds mental illness, then we can begin to have open and honest communication about pain and suffering, and those in need can receive the help they deserve.
Keywords: Public health; Social media; Mental health